Optimization of DIC-Tripolium Ecofriendly Extraction Process: Recovery of Hesperidin from Orange Byproducts, Antioxidant and α-Amylase Inhibition of Extracts - Mariem Ben Abdallah; Morad Chadni; Nouha M’hiri; Fanny Brunissen; Nesrine Rokbeni; Irina Ioannou; Karim Allaf; Colette Besombes; Nourhene Boudhrioua (Antioxidants, 2023)
This study aimed to investigate the effect of an innovative ecofriendly process—instant controlled pressure drop technology, also known as “détente instantanée contrôlée” or DIC—coupled with Tripolium extraction (DIC-Tripolium), on the hesperidin recovery, and antioxidant and antidiabetic activities of orange byproduct extracts. A DIC pretreatment was applied to partially dried orange byproducts (~16% wet basis). A central composite rotatable design (CCRD), composed of 13 experimental trials (four factorial points, four-star points, and five repetitions for the central point), was followed by a Tripolium process consisting of successive intermittent extraction periods using ethanol/water solvent at 20 ± 1 °C, 5 kPa for 5 min and m/v ratio = 5 g/50 mL. The DIC pretreatment, coupled with the Tripolium process, increased the extractability of hesperidin (from 1.55- to 4.67-fold compared to untreated DIC orange byproducts). The radical scavenging activities of the extracts were also enhanced or preserved in different DIC–Tripolium extracts. The α-Amylase inhibition percentage varied between 55.6 ± 0.02 and 88.30 ± 0.01% according to DIC–Tripolium conditions. The multi-criteria optimized condition of DIC–Tripolium extraction, allowing for the maximization of the hesperidin content, radical scavenging activities, iron chelating activity, and α-amylase inhibition of extracts, corresponds to a DIC saturated steam pressure of 599.4 kPa and a DIC pretreatment time of 38 s.